The Influence of Partai Solidaritas Indonesia (PSI) Positioning Toward Brand Awareness on Novice Voters in West Java - Jasmine Alya Pramesthi; Berlian Primadani Satria Putri (Jurnal Riset Komunikasi, 2019)
If the positioning of a political party has been deemed right on target, of course, the target market targeted by the political party feels familiar or aware of the presence of the political party, especially if the political party is newly established to bring up brand awareness of the political party. One of the new political parties competing in the 2019 General Election is the Indonesian Solidarity Party (PSI). As a new participant party in the 2019 General Election, PSI tried to form a position in the minds of the public as a millennial party. The purpose of this study was to determine the positioning of PSI as measured by positioning dimensions, namely the points of difference and points of parity that have an influence on brand awareness as measured by its level, namely unaware brand, brand recognition, brand recall, and top of mind in the novice voter in West Java. This research uses quantitative research methods with the type of inferential research. Data from this study were distributed through online questionnaires. The sampling technique of this study is probability sampling with a simple random sampling method. Data were analyzed using a simple linear regression test through the IBM SPSS version22. From the results of data analysis that has been done shows that the positioning of PSI (X) significantly influences brand awareness of 0.44 or 44% while 56% of other factors are not explained in this study.